PENGARUH STORE ATMOSPHERE TERHADAP MINAT BELI KONSUMEN PADA DEPATI VII KOPI KOTA SUNGAI PENUH (KERINCI) - Muhammad Fauzi; Mohd Fauzan; Mursal (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2022)
This study aims to examine the effect of Store Atmosphere which consists of Instore Atmosphere(store inside settings) and Outstore Atmosphere(outside store settings) on consumer buying interest in Depati VII Kopi, Sungaipuh City (Kerinci). The research utilizes primary data, accompanied by a Multiple Linear Regression model as a quantitative data analysis tool. This study shows that the Instore Atmosphere and Outstore Atmosphere have a significant effect on the buying interest of Depati VII Coffee consumers, either partially or simultaneously. Finally, opening up space and tracing for further research, by making more in-depth (specific) studies, because much has not been revealed in Depati VII Kopi.